PLAN ESTRATÉGICO PARA PROMOVER EL TURISMO SOSTENIBLE EN EL CENTRO DE RECREACIÓN “LA EMILY” DEL CANTÓN MOCACHE DEL AÑO 2022 - Pluas Morales, Genesis Fiorella (2022)
The strategic plans that are designed for the organizations of today's world, are fundamental processes and tools that all types of companies do not matter in the market that they develop, they are structured and very well defined to achieve the outlined goals. This research focuses on designing a strategic plan to promote sustainable tourism in the "La Emily" recreation center in the Mocache canton. Taking advantage of the natural environment, location so that clear proposals are planted, focused on making the tourist place known as a way not only to have fun, but to relate to nature. For the development of the project, descriptive, explanatory, field research methods that analyze the strategies to be implemented in the strategic plan will be used, the survey technique on sustainable tourism will also be included, concluding the importance of the development of the plan. strategy as a viable, reliable and acceptable alternative seeks to determine the techniques and skills to promote tourism in the recreation center "La Emily" benefiting the entire community.